Membros: v. 4, n. 2 (2006) - ., .. (RENOTE, 2006)
Cleusa Maria Maximino Carvalho Alonso - UFSM Gilse Antoninha Morgental Falkembach - UNIFRA Julio Alberto Nitzke - SEAD/UFRGS Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Liliana Passerino - FEEVALE Magda Bercht - Instituto de Informática/UFRGS Mára Lúcia Fernandes Carneiro - Instituto de Psicologia/UFRGS Marcelo Foohs - UERGS Marcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Maria Alice Gravina - Instituto de Matemática/UFRGS Marlise Geller - ULBRA Patrícia Alejandra Behar - Faculdade de Educação/UFRGS Ricardo Azambuja Silveira - UFSC Rosa Maria Vicari - Instituto de Informática/UFRGS Roseclea Medina - UFSM Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS